Experimental Study on Damage Monitoring of FRP Plate Using FBG Sensors - Zhe Zhang; Tongchun Qin; Yuping Bao; Ronggui Liu; Jianping He (Micromachines)
With the widespread application of FRP (Fiber Reinforced Plastics) materials in fields such as wind turbine blades and ships, the safety performance of these materials during their service life has garnered signification attention. This study employs the fiber Bragg grating (FBG) sensor to monitor damage of the FRP materials. An FRP plate embedded with six FBGs was fabricated, and different degrees of damage were induced in the FRP plate. The six FBGs measured the damage information of the FRP plate under impulse and continuous sinusoidal vibration loads. The results demonstrate that both the strain information and the frequency shift information measured by the FBG sensors can effectively and sensitively identify damage in the FRP plate.